Comparative analysis of the performance of bioretention implementation at a roadside area in Malaysia. Issue 4 (29th July 2021) - Nor, Nurul Afiqah Lotfi; Kamal, Norashikin Ahmad; Park, Heekyung
Abstract : Low-impact development is used to shift from a conventional method to a more sustainable method for managing stormwater run-off. Among the most described and practicable methods is bioretention, which mimics the natural process. Therefore, this study aims to investigate the effectiveness of bioretention as a stormwater management strategy, focusing on a roadside area of Universiti Teknologi Mara (UiTM), Malaysia. The design for the bioretention was adopted from Manual Saliran Mesra Alam guidelines. The rainfall–run-off relationship was determined using an implementation of Stormwater Management Model 5.1. The results for the cases with and without the presence of the bioretention system were then compared in terms of percentage volume run-off reduction and its peak flow. Based on the simulation analysis from this study, it was found that the implementation of bioretention on the roadside area of UiTM Shah Alam led to a significant reduction in stormwater run-off quantity and peak flow, reflecting two different percentage values of contributing drainage area of 2 and 4%. Although the capital cost of bioretention would be higher for the initial stage of implementation, it would require minimal maintenance compared with the conventional method.